KEBIJAKAN PEMERINTAH REPUBLIK INDONESIA TENTANG DWIKEWARGANEGARAAN ETNIS TIONGHOA PADA MASA DEMOKRASI LIBERAL - Resti Ratnawati; Iskandar Syah; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2013)
Abstract: Based on the formulation of the problem, is the driving factor of the Government'spolicy of Dwikewarganegaraan Indonesia ethnic Chinese Then, this research is aimed at findingthe driving factor of the Government's policy of the Republic of Indonesia concerning theDwikewarganegaraan ethnic Chinese. The methods used in this research are the historicalmethod. Data collection techniques using the technique of documentation and library techniqueswhile data analysis techniques is qualitative data analysis techniques. The results of the analysisof the data in this thesis is the ethnic Chinese in Indonesia has Dwikewarganegaraan, thedominance of ethnic Chinese in Indonesia in economic activity system of dualism ethnicChinese income tax in Indonesia. From the results of the deliberations conducted by the authorof the birth of the Government policy of driving factor of the Republic of Indonesia concerningthe Dwikewarganegaraan ethnic Chinese, then it can be obtained, conclusions the incidence ofdual citizenship was due to two deciding system defining citizenship is different in the twocountries, ethnic Chinese dominate economic activity in Indonesia reached 70%, ethnic Chinesewho had the dwikewarganegaraan which has to pay income tax in two countries Indonesia andChinese in accordance with an annual income.Keywords: Government policy about RI Dwikewarganegaraan.ABSTRAKAbstrak: Berdasarkan rumusan masalah, apakah Faktor pendorong lahirnya KebijakanPemerintah Indonesia tentang Dwikewarganegaraan Etnis Tionghoa Maka, penelitian iniditujukan untuk mencari faktor pendorong lahirnya Kebijakan pemerintah Republik Indonesiatentang Dwikewarganegaraan Etnis Tionghoa. Metode yang digunakan dalam penelitian iniadalah metode historis. Teknik pengumpulan data menggunakan teknik dokumentasi dan teknikkepustakaan sedangkan teknik analisis data merupakan teknik analisis data kualitatif. Hasilanalisis data dalam skripsi ini adalah Etnis Tionghoa di Indonesia mempunyaiDwikewarganegaraan, dominasi Etnis Tionghoa dalam kegiatan ekonomi di Indonesia sistemdualisme pajak penghasilan Etnis Cina di Indonesia. Dari hasil pembahasan yang dilakukan olehpenulis menganai faktor pendorong lahirnya kebijakan Pemerintah Republik Indonesia tentangDwikewarganegaraan Etnis Tionghoa, maka dapat diperoleh kesimpulan, timbulnyakewarganegaraan ganda itu karena adanya dua sistem penentu kewarganegaraan yang berbedadi kedua negara, Etnis Tionghoa mendominasi kegiatan ekonomi di Indonesia mencapai 70%,Etnis Tionghoa mempunyai dwikewarganegaraan yang harus membayar pajak penghasilan didua negara Indonesia dan Tionghoa sesuai dengan pendapatan pertahunnya.Kata kunci: Kebijakan pemerintah RI tentang Dwikewarganegaraan